Research progress, exploration process, and challenges in marine sandy hydrates - Qi FAN; Qiang FU; Gang GUO; Zhenyu ZHU; Weixin PANG; Qingping LI; Haiteng ZHUO (Shiyou shiyan dizhi)
Natural gas hydrates are a key area of development in marine energy resources. However, the technical and economic barriers for muddy silt gas hydrate exploration in the South China Sea are high, and their resource potential remains controversial. This paper reviews the significant advancements achieved in China, the United States, and Japan over the past 20 years in the exploration of marine sandy hydrates. It discusses three primary hydrate types, i.e., muddy silt pore-filling, muddy silt fracture-filling, and sandy pore-filling hydrates, and summarizes the characteristics of sandy hydrates based on core samples, well logging, and laboratory findings. This paper presents the exploration and evaluation procedures for the "hydrate accumulation system" and discusses the challenges such as non-diagenetic reservoir evaluation, temperature-pressure variations, geomechanics, and pressure-preserved coring. Results reveal that sandy pore-filling hydrates (extendable to silt-sized particles) are currently the only hydrate type with economic value, characterized by high saturation (40% to 90%), high resistivity, strong formation strength, high quartz content (56% to 77%), and higher median particle size (approximately 56 to 87 μm). Those hydrates are typically well-sorted silty deposits in white-gray or black-gray, with a frosted texture and pore structure development. It is recommended to enhance the popularization and application of the "hydrate accumulation system" in the exploration of sandy hydrates and further address the issues in non-diagenetic reservoir evaluation, phase transitions due to temperature-pressure changes, complex geomechanical problems, and pressure-preserved coring technology. In conclusion, a reassessment of hydrate resource value is needed to provide a theoretical and scientific basis for the co-production of natural gas and gas hydrates.